Shariati and the Reconstruction of Social Sciences - Mohammad Yadegari (International Institute of Islamic Thought, 1984)
Ali Shariati was a Muslim reformer who laid much of the intellectual groundwork for the Iranian revolution of 1979. His inspiring speeches and written works aroused the people, particularly the students, to the state, where they were easily mobilized by Khomeini and his co-workers. Killed by the Shah’s agents in London in 1977, he is still remembered as a great martyr to their cause. His ideas on the nature of Islam are of interest to us today. Ali Shariati was born in 1933 in the village of Mazinan near Sabzawar in Khurasan, Iran. He came from a family whose members were known for their scholarship, knowledge, and righteousness. He attended the Teacher’s Training School, and taught in high school for some years before pursuing graduate work in Europe. He was also active in his father’s Center for the Propagation of Islamic Truth. Shariati’s views were greatly influenced by his learned father who was fortunate enough to acquire a personal library of nearly two thousand books. He was also influenced by the political events in Iran, especially during Dr. Muhammad Mosaddeq’s premiership, and by the various underground movements after the fall of Mossadeq in 1953. Particularly important was the Muslim Socialist Movement founded in the early 1940’s in Tehran. This group believed in Islamic ideals but emphasized the socialistic tendencies of its economic system. In the manner of Amir Ali, the author of Spirit of Islam, Shariati wanted to emulate the lives and ideas of early Muslims whom he admired. He often referred to Prophet Muhammad, Abu Dhar al-Ghaffari, Ali, Husayn, and others as men who ought to be followed as examples. In his formative years, he was influenced by many people including Frantz Fanon, al-Afghani, Taleqani, and Muhammad Iqbal. In my opinion, Shariati was more influenced by Iqbal than any other’ scholar, whether in the East or the West. I have pointed out this influence in my book, Ideological Revolution in the Muslim World ...